Mosaic trisomy 13 and a sacral appendage (2013)
Mosaic trisomy 13 occurs when there is a percentage of trisomic cells for an entire chromosome 13, while the remaining percentage of cells is euploid. The prevalence of this syndrome ranges from 1 in 10 000 to 1 in 20 000 births. Complete, partial or mosaic forms of this disorder can occur. The phenotype of mosaic trisomy 13 patients varies widely. Patients with mosaic trisomy 13 usually have a longer survival and a less severe phenotype compared to patients with complete trisomy 13. Genetic counselling is difficult due to the wide variation among the clinical manifestations of these patients. There have been 49 cases of mosaic trisomy 13 reported in the literature. We report the case of a patient with mosaic trisomy 13, a sacral appendage and a cleft lip and palate. Copyright 2013 BMJ Publishing Group. All rights reserved.